Typology of Arabic Language Learning in Three Regional Pesantren: A Phenomenological Study and Its Implementation in Contextual Curriculum Development - Muttaqin, Zainul; Akbar , Mochhammad Andi; Fitri , Agustina Aidatul; Daroini, Slamet (Al-Muhawaroh: Jurnal Pendidikan Bahasa Arab, 2026)
This study investigates Arabic language learning in Indonesian pesantrens as a social phenomenon reflecting diverse traditions, institutional orientations, and cultural contexts. The research agenda aims to map learning typologies across Java, Sumatra, and Lombok, while analyzing how students lived experiences inform adaptive curriculum development. Methodologically, this study employs a qualitative phenomenological configuration with three alumni as primary informants. Data were analyzed through a rigorous inductive process including bracketing, horizontalization, and essence synthesis to ensure empirical validity. The findings reveal three distinct regional typologies: Dalwa (Java) prioritizes muhadatsah within a rigorous bi’ah lughawiyah; Al-Ittifaqiah (Sumatra) utilizes a formal-prescriptive system of vocabulary targets and sanctions; while institutions in Lombok demonstrate an integrative model combining communicative practices with traditional foundations. Interpretive conclusions, framed through Ralph W. Tyler’s and Lawrence Stenhouse’s theories, emphasize that student experiences transform Arabic from a linguistic tool into a core dimension of religious identity and spiritual motivation. This study synthesizes these outcomes into a curriculum framework that balances formal structure with process flexibility, integrates tradition with innovation, and prioritizes an affective-spiritual orientation to produce an adaptive, inclusive, and globally competitive Arabic curriculum that remains deeply rooted in the pesantren tradition.